2022
DOI: 10.2478/acve-2022-0013
|View full text |Cite
|
Sign up to set email alerts
|

Diet Supplementation Helps Honey Bee Colonies in Combat Infections by Enhancing their Hygienic Behaviour

Abstract: The hygienic behavior in honey bees is a complex polygenic trait that serves as a natural defense mechanism against bacterial and fungal brood diseases and Varroa destructor mites infesting brood cells. The aim of this study was to evaluate the effect of a dietary amino acids and vitamins supplement “BEEWELL AminoPlus” on hygienic behavior of Apis mellifera colonies combating microsporidial and viral infections. The experiment was performed during a one-year period on 40 colonies alloted to five groups: one su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 97 publications
0
10
0
Order By: Relevance
“…These results are in agreement with the report of Highfield et al (2009) that DWV may persist independently of Varroa infestations. Besides, in spreading viral infections, other factors, such as virus contamination of food, virulence of the DWV and ABPV, horizontal transfer of infection from bee to bee, could also play roles ( de Miranda et al, 2011 ; Locke et al, 2012 ; Stanimirović et al, 2019 ; Stanimirovic et al, 2022a ). Another explanation of the significant increase in ABPV and DWV level in our study could be related with recorded changes in the expression levels of some immune-related genes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are in agreement with the report of Highfield et al (2009) that DWV may persist independently of Varroa infestations. Besides, in spreading viral infections, other factors, such as virus contamination of food, virulence of the DWV and ABPV, horizontal transfer of infection from bee to bee, could also play roles ( de Miranda et al, 2011 ; Locke et al, 2012 ; Stanimirović et al, 2019 ; Stanimirovic et al, 2022a ). Another explanation of the significant increase in ABPV and DWV level in our study could be related with recorded changes in the expression levels of some immune-related genes.…”
Section: Discussionmentioning
confidence: 99%
“…The honey bee mite V. destructor (Acari: Varroidae), is considered the most damaging parasite of the honey bee A. mellifera L. ( Carreck et al, 2010 ; Guzmán-Novoa et al, 2010 ; Le Conte et al, 2010 ; Jack and Ellis 2021 ). Being distributed nearly all around the world, Varroa is the leading cause of honey bee colony weakening and loss ( Genersch et al, 2010 ; Rosenkranz et al, 2010 ; Stanimirović et al, 2019 , 2022a ; Noël et al, 2020 ; Traynor et al, 2020 ; Boncristiani et al, 2021 ). As an obligate ectoparasite of A. mellifera bees, Varroa causes serious health problems of the host due to feeding on the fat body and haemolymph of adult and developing honey bees ( Rosenkranz et al, 2010 ; Ramsey et al, 2019 ) and the role of mechanical or biological vector of pathogene microorganisms, especially viruses, with a potencial to exacerbate preexisting infections ( Genersch and Aubert, 2010 ; Glavinić et al, 2014 ; McMenamin and Genersch 2015 ; Noël et al, 2020 ; Traynor et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are few countries in the world where fumagillin is registered for use, and it is worth looking for some alternatives in the fight against nosemosis. Many studies have been conducted and proved that dietary supplements can exert an immunostimulating and/ or immunoprotective effect as well as other beneficial effects (Jovanovic et al, 2021;Stanimirovic et al, 2022). It has been demonstrated that adding vitamin C to the winter bee diet has some protective effect, particularly against diseases where oxidative stress is a major factor (Farjan et al, 2012), that caffeine can reduce the harmful effect of pesticides (Balieira et al, 2018), and that Agaricus blazei and Agaricus bisporus extracts increase the expression of most immune-related genes (Glavinic et al, 2021a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous acaricides are available for the treatment of Varroa mites ranging from synthetic, or “hard”, to naturally derived, or “soft”, agents [ 1 , 9 ]. The major disadvantages of synthetic acaricides are their toxic side effects on bee colonies and the occurrence of chemical residues in bees and their products [ 10 , 11 , 12 ]. Accumulation of acaricide residues in wax and other bee products may accelerate the development of resistance to V. destructor , due to prolonged exposure of parasites to low doses of acaricides [ 1 ].…”
Section: Introductionmentioning
confidence: 99%